2019
DOI: 10.22454/fammed.2019.845581
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Barriers for Family Physician Contribution to the Maternity Care Workforce

Abstract: Background and Objectives: The number of family physicians providing obstetric deliveries is decreasing, but high numbers of new graduates report they intend to include obstetric deliveries in their practices. The objective of this study was to understand barriers to providing obstetrical care faced by recent family medicine residency graduates who intended to provide obstetrical care at graduation. Methods: Email surveys were sent to graduating family medicine residents who indicated intention to include obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…18 While only 8% of current family physicians include OB in their practice, nearly 22% of recent graduates intend to include OB in their practice. 19 While conducting a qualitative study of recent family medicine graduates to better understand the motivating factors and barriers faced by FPs who want to include obstetric deliveries in their practice, 20,21 we found that almost all participants discussed the concept of burnout related to practicing OB. We aimed to explain how and why practicing OB might be associated with lower levels of burnout 13 by examining the ways in which FPs discussed the relationship between practicing OB and burnout.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…18 While only 8% of current family physicians include OB in their practice, nearly 22% of recent graduates intend to include OB in their practice. 19 While conducting a qualitative study of recent family medicine graduates to better understand the motivating factors and barriers faced by FPs who want to include obstetric deliveries in their practice, 20,21 we found that almost all participants discussed the concept of burnout related to practicing OB. We aimed to explain how and why practicing OB might be associated with lower levels of burnout 13 by examining the ways in which FPs discussed the relationship between practicing OB and burnout.…”
Section: Resultsmentioning
confidence: 93%
“…As reported in detail elsewhere, 20,21 in 2017, we conducted semistructured telephone interviews with 56 recent family medicine graduates to understand intention to include OB in their practice. We used data from the American Board of Family Medicine (ABFM) to identify and recruit all FPs who graduated from residency between 2014 and 2016 and who, upon registering for their Board certification exam, indicated that they planned to include obstetric deliveries in their practice.…”
Section: Methodsmentioning
confidence: 99%
“…While those currently including obstetric deliveries were significantly more likely to agree to be interviewed than those not including obstetrics (63.7% and 40.5%, respectively, p<0.001); we interviewed (N=56) a balanced sample from each group, 29 currently delivering babies and 27 not currently delivering babies. Table 1 includes demographic information about the interviewees (more detailed survey findings are reported elsewhere27).…”
Section: Resultsmentioning
confidence: 99%
“…This mixed-methods exploratory study, conducted in 2017, included a brief electronic survey and individual, semistructured interviews. A five-question survey was sent to all 2098 family physicians who graduated from residency between 2014 and 2016 who reported intention to include obstetric deliveries in practice on the American Board of Family Medicine (ABFM) Certification Examination Registration Practice Demographic Questionnaire (full survey analysis and findings have been reported elsewhere27). Family physicians in the same cohort who did not indicate intention to include obstetrics in practice were excluded from the study (n=7451).…”
Section: Methodsmentioning
confidence: 99%
“…In this issue of Family Medicine, Barreto and colleagues report the results of a survey of 2,098 residency graduates who took the American Board of Family Medicine certification exam between 2014 and 2016 and who stated they intended to include maternity care in their future practices. 2 Forty-eight percent (1,016) responded to the survey and 68.9% of those responding reported they had entered practices that included maternity care after residency. The study then focused on the 316 graduates who did not enter practices with maternity care in spite of having indicated their intention to do so.…”
mentioning
confidence: 99%